RoboCup 2010 Robot Soccer World Cup XIV - Ruiz-del-Solar, Javier; Chown, Eric.; Plöger, Paul G.; SpringerLink (Online service). (aBerlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book includes the thoroughly refereed post-conference proceedings of the 14th RoboCup International Symposium, held in Singapore, in June, 2010 - representing the scientific tracks structured in four sessions entitled simulation and rescue robots; robot perception and localization; robot motion and humanoid robots; and human robot interaction and semantic scene analysis. The 20 revised full papers and 16 revised short papers presented were carefully reviewed and selected from 78 submissions. Documenting the research advances of the RoboCup community since the predecessor symposium, this book constitutes a valuable source of refrence and inspiration for R&D professionals interested in RoboCup or in robotics and distributed AI more generally
aEntropy-Based Active Vision for a Humanoid Soccer Robot -- A Realistic Simulation Tool for Testing Face Recognition Systems under Real-World Conditions -- Thermal Face Recognition Using Local Interest Points and Descriptors for HRI Applications -- On Progress in RoboCup: The Simulation League Showcase -- Odometry Correction for Humanoid Robots Using Optical Sensors -- SSL-Humanoid: RoboCup Soccer Using Humanoid Robots under the Global Vision -- Localization with Non-unique Landmark Observations -- MR-Simulator: A Simulator for the Mixed Reality Competition of RoboCup -- Learning Footstep Prediction from Motion Capture Kicking a Ball ? Modeling Complex Dynamic Motions for Humanoid Robots -- Towards Semantic Scene Analysis with Time-of-Flight Cameras -- Providing Ground-Truth Data for the Nao Robot -- Optimizing Particle Filter Parameters for Self-localization -- Improving People Awareness of Service Robots by Semantic Scene Knowledge -- An Evaluation of Open Source SURF Implementations -- A Semantic World Model for Urban Search and Rescue Based on Heterogeneous Sensors -- Improving Biped Walk Stability Using Real-Time Corrective Human Feedback -- A Review of Shape Memory Alloy Actuators in Robotics -- Biologically Inspired Mobile Robot Control Robust to Hardware Failures and Sensor Noise -- TopLeague & Bundesliga Manager New Generation Online Soccer Games -- Human vs. Robotic Soccer: How Far Are They? A Statistical Comparison -- Learning Powerful Kicks on the Aibo ERS-7: The Quest for a Striker -- Real-Time Active Vision by Entropy Minimization Applied to Localization -- Multi-agent Behavior Composition through Adaptable Software Architectures and Tangible Interfaces -- A Novel Real-Time Local Visual Feature for Omnidirectional Vision Based on FAST and LBP -- Mixed 2D/3D Perception for Autonomous Robots in Unstructured Environments -- Hierarchical Multi-robot Coordination -- Biped Walking Using Coronal and Sagittal Movements Based on Truncated Fourier Series -- Realistic Simulation of Laser Range Finder Behavior in a Smoky Environment -- Cooperative Localization Based on Visually Shared Objects -- Parameter Optimization of a Signal-Based Omni-Directional Biped Locomotion Using Evolutionary Strategies -- Designing Effective Humanoid Soccer Goalies -- A Supporter Behavior for Soccer Playing Humanoid Robots -- Utilizing the Structure of Field Lines for Efficient Soccer Robot Localization -- Robot Detection with a Cascade of Boosted Classifiers Based on Haar-Like Features -- LearnPNP: A Tool for Learning Agent Behaviors.
Electronic reproduction.
Keywords: Robotics -- Congresses; Electronic books